Aktivitas Antimikroba Khamir Asal Dadih (susu kerbau fermentasi) Terhadap Beberapa Bakteri Patogen - Yurliasni Yurliasni (Agricultural Faculty, 2010)
Antimicroba activity of yeast dadih (buffalo milk fermentation) origin on pathogenic bacteriaABSTRACT. Research was carried out to study the effect of antimicrobial activity of yeast found in dadih. Yeasts chosen were isolated from dadih (traditionally buffalo milk fermentation). The objective is to know the ability of yeast to inhibit the growth of pathogenic bacteria in milk. They were Candida curiosa, Brettanomyces custersii, and Kluyveromices lactis. Kluy. lactis has strong antimicrobial on Bacillus subtilis with zone of inhibition 5mm, C. curiosa on E.coli (5mm) and C. curiosa and Brett. custersii also have strong antimicrobial on S. aureus consecutively 5,75 and 7 mm. As a conclusion the result showed that all of three yeasts selected have capability to stop the growth of pathogenic bacteria of buffalo milk origin in five days.